COGNITIVE BEHAVIORAL THERAPY FOR TREATING ANXIETY DISORDERS: EFFICACY AND FUTURE DIRECTIONS - Sana Zafar (Global Journal of Multidisciplinary and Applied Sciences, 2024)
Anxiety disorders represent one of the most prevalent mental health conditions worldwide, with significant implications for an individual's emotional, social, and occupational functioning. Cognitive Behavioral Therapy (CBT) has emerged as one of the most effective therapeutic interventions for treating anxiety disorders, including generalized anxiety disorder, panic disorder, social anxiety disorder, and specific phobias. This article aims to explore the efficacy of CBT in treating anxiety disorders, with a focus on the latest advancements and future directions in this therapeutic modality. Furthermore, it will examine the application of CBT in Pakistan, where mental health treatment is increasingly gaining recognition but faces several challenges. This paper concludes with recommendations for integrating CBT into the broader mental health care framework in Pakistan and beyond.